Exam ref 70-697 : configuring Windows devices - Bettany, Andrew; Warren, Andrew (Pearson Education : Microsoft Corporation, 2018)
Prepare for Microsoft Exam 70-697-and help demonstrate your real-world mastery of configuring Windows 10 devices in the enterprise. Designed for experienced IT professionals ready to advance their status, this Exam Ref focuses on the critical-thinking and decision-making acumen needed for success at the MCSA level. Focus on the expertise measured by these objectives: " Manage identity " Plan desktop and device deployment " Plan and implement a Microsoft 365 Solution " Configure networking " Configure storage " Manage data access and protection " Manage remote access " Manage apps " Manage updates and recovery This Microsoft Exam Ref: " Organizes its coverage by exam objectives " Features strategic, what-if scenarios to challenge you " Assumes you have experience with Windows desktop administration, maintenance, and troubleshooting; Windows 10 security, and integrated Azure features; as well as a basic understanding of Windows networking, Active Directory, and Microsoft Intune For details on requirements for taking Exam 70-697, go to https://www.microsoft.com/en-us/learning/exam-70-697.aspx